Genotoxic effects of panoramic radiation by assessing the frequency of micronuclei formation in exfoliated buccal epithelium - KB, Vidya; Kalappanavar, Anupama N.; M, Muniyappa (International Journal of Research in Medical Sciences, 2017)
Background:Panoramic radiography is one of the most commonly used radiographic methods to complement clinical examination. Ionizing radiation is a well-known mutagen and carcinogen in the human population. So this study was undertaken to evaluate the possible genotoxic effects of panoramic radiation by assessing the frequency of micronuclei formation in the exfoliated buccal epithelium. Methods:50 patients of either sex in the age range of 15 to 75 years with apparently normal oral mucosa with no adverse habits and without any oral lesions were included in the present study after their consent. Buccal epithelial cells were obtained from the buccal mucosa by scraping with the toothbrush immediately before and after 10 ± 2 days of exposure to panoramic radiography. Cytological preparations were stained and observed under microscope. Student’s paired‘t’ test was used for the comparison between mean frequency of micronuclei in buccal epithelial cells in patients before and after panoramic radiography. Results:Significant increase (P <0.0001) in the frequency of cells with micronuclei and total number of micronuclei after panoramic radiography was detected. Conclusion:The X-radiation emitted during panoramic radiography does induce some genotoxic changes in the form of increased frequency of micronuclei in target buccal epithelial cells.